ANARCHISM AND JUSTICE IN CASE OF SOUTH AFRICA VS ISRAEL - Ambarwati; Subarno; Lusi Andryani (European Journal of Humanities and Educational Advancements, 2024)
In response to the outbreak of war between Palestinian – Israel in October 2023, many of the countries in the world try to curse and criticize toward Israel. On the other side they support Palestinian people by giving material support and political support as well as diplomatic one through international organizations in order to end people suffering in the area of Palestine. South Africa as a non-involved of the conflict made a surprising action by filing lawsuit against Israel by accusing Israel committed to do genocide.